Stress, anxiety and depression in the elderly in relation to family functionality - Macas Ordoñez, Brigitte Danyeli (2023)
Objective. To identify the relationship between family functioning and the presence of anxiety, depression and stress in older adults in Santo Domingo de los Colorados (Ecuador). Methods. The research was developed under a quantitative research paradigm, of correlational scope and cross-sectional design. The study sample consisted of 384 older adults from Santo Domingo de los Colorados, who were administered a survey composed of 32 questions. Five questions measured demographic aspects of the participants, 21 measured mental health levels (DASS 21) and 5 measured family functionality (APGAR). Cronbach's alpha tests were used to measure the reliability of the instrument and cross-data contingency tables, normality tests and bivariate correlational analyses were developed for data analysis. All these analyses were developed using SPSS21. Results. The study showed that 92% of the respondents live in functional families. However, 47.9% presented prevalence of anxiety (-.190** p < 0.05), 33.3% depression (-.246** p < 0.05) and 29.4% stress (-.139** p < 0.05), in the older adults of Santo Domingo de los Colorados. Conclusions. Family functionality has an inverse influence on the mental health of older adults, from which it can be inferred that the higher the family functionality, the lower the presence of anxiety, depression and stress.